Conversion of straw to nitrogen doped carbon for efficient oxygen reduction catalysts in microbial fuel cells. Issue 109 (21st October 2015) - Liu, Lang; Xiong, Qi; Li, Chungen; Feng, Yan; Chen, Shuiliang
Abstract : Nitrogen-doped carbon with high nitrogen content was prepared from rice straw through a three-step process, including hydrothermal, freeze drying and heat-treatment in NH3, and was used as a high-efficient oxygen reduction reaction catalyst in MFCs. Abstract : The exploration of highly-efficient and low-cost oxygen reduction reaction (ORR) catalysts was still a major task for microbial fuel cells (MFCs). Herein, we report the conversion of cheap and widely available biomass to nitrogen-doped carbon (NC) for highly-efficient ORR catalysts in air-cathode MFCs. The NC was prepared from rice straw through a three-step process, including hydrothermal carbonization, freeze drying and heat-treatment in NH3 . The NC had a high nitrogen content of 5.57 at% and showed outstanding catalytic activity for ORR. The MFC based on the NC generated a high maximum power density of 2300 mW m −2, which was much higher than that of the Pt/C.